Cytokine profiling in human colostrum and milk by protein array - Kverka, Miloslav; Burianova, Jaroslava; Lodinova-Zadnikova, Raja; Kocourkova, Ingrid; Cinova, Jana; Tuckova, Ludmila; Tlaskalova-Hogenova, Helena (Clinical chemistry, 2007)
BACKGROUND: Human colostrum and milk contain components that influence development. Our aim was to use a protein array to determine the cytokine profile of human lacteal secretions and changes that occur during the early postpartum period. METHODS: We collected 17 samples of colostrum during the first 2 days postpartum and a 2nd group of 5 sets of 2 to 3 sequential colostrum or milk samples (at 20- to 30-h intervals). We analyzed the samples with array membranes consisting of 42 or 79 antibodies directed against cytokines. RESULTS: In most samples, we detected the previously described cytokines interleukin-8 (IL-8)/CXCL8, epidermal growth factor (EGF), growth-related oncoprotein (GRO)/CXCL1-3, angiogenin, transforming growth factor beta-2, and monocyte chemotactic protein 1 (MCP-1/CCL2). In addition, we found 32 cytokines that have not been described before in colostrum. Cytokine concentrations differed among mothers, and the spectrum of cytokines changed with time after delivery. A significant decrease occurred in IL-12 and macrophage inflammatory protein-1delta/CCL15 and a significant increase in MCP-1/CCL2. The production of angiogenin, vascular endothelial growth factor, GRO/CXCL1-3, EGF, and IL-8/CXCL8 remained high throughout. The concentrations of 2 selected cytokines measured with the array technique and ELISA showed moderate to strong correlation (r = 0.63 for EGF and r = 0.84 for IL-8/CXCL8). CONCLUSION: Despite the lack of precise quantification, the protein array might be suitable for cytokine screening. It allows simultaneous detection of a broad spectrum of cytokines (including those not described before) in lacteal secretions.
Keywords: mezibuněčné signální peptidy a proteiny; poporodní období; proteomika; Colostrum; Postpartum Period; Time Factors; Milk, Human; cytokiny; Intercellular Signaling Peptides and Proteins; chemokiny; Adult; Cytokines; Proteomics; čipová analýza proteinů; ženské pohlaví; ELISA; mateřské mléko; Protein Array Analysis; Humans; časové faktory; Chemokines; kolostrum; Enzyme-Linked Immunosorbent Assay; dospělí; Female; lidé